2019
DOI: 10.1016/j.anorl.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of head and neck cancer on partner's sociability

Abstract: Introduction"Sociability" is defined as the range of experiences linking the subject to others. This is the first study to focus specifically on the impact of head and neck cancer on the sociability of patients' partners. MethodData were collected via a dedicated questionnaire sent to patients' partners. The main endpoint was partner's self-assessment of the impact of the patient's disease on the partner's everyday life. The impact on sociability was analyzed with respect to: the circle of friends (friendship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…Additionally, the main factor behind oral cancer therapy delays is patient delays-additionally, tertiary and secondary delays, which are also known as competent inefficiencies, exist. 15 The non-association is comparable to the research done by Osazuwa-Peters et al, 11 but they reported a diagnosis in addition to treatment initiation. Our environment has a trait called late hospital presentation, which has a significant impact on patient outcomes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, the main factor behind oral cancer therapy delays is patient delays-additionally, tertiary and secondary delays, which are also known as competent inefficiencies, exist. 15 The non-association is comparable to the research done by Osazuwa-Peters et al, 11 but they reported a diagnosis in addition to treatment initiation. Our environment has a trait called late hospital presentation, which has a significant impact on patient outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding socioeconomic conditions, as indicated in Table 1. The majority of patients (28) from high-class families presented early, compared to (11) patients from middleclass families who presented late, and all (21) patients from lower-class families who presented late. The education level reveals that the majority of patients (31), who were educated, attended a school for more than a year, but only up to ten (matriculate or similar) years, or advanced literacy: got a college-or university-level education, and they displayed early presentation.…”
Section: Figure 1: Frequency Distribution Of Size Of Massmentioning
confidence: 99%
“…Everyday sociability and activities considerably change for partners of patients with HNC [21,22]. This study's specific focus on social activities for FMs that occurred around food or eating and drinking, identified that FMs socialise less due to the patient's functional and psychological changed relationship with food.…”
Section: Discussionmentioning
confidence: 99%
“…L’explication tient peut-être dans le fait que ces patients et notamment ceux COVID + se satisfaisaient plus que les autres de leur état et semblaient soulagés d’avoir évité une complication d’une infection comme une hospitalisation en réanimation. Ils semblent aussi avoir moins souffert du confinement car peut-être étaient-il habitués à une sociabilité réduite [5] . D’autre part le port du masque a sans doute facilité le contact avec autrui par le masquage des séquelles des cancers et des traitements.…”
unclassified